Parental Confirmation and Emerging Adult Children’s Body Image: Self-Concept and Social Competence as Mediators - Taniguchi, Emiko and Dailey, René M. (Communication Research, 2020)
Through a lens of confirmation theory, this study examined how parental confirmation acceptance and challenge was related to emerging adults’ body image, and how these associations were mediated by social competence and self-concept. This study also examined whether the hypothesized links differed by parental and child sex. Male and female college students ( N = 447) completed an online questionnaire. A multiple-group analysis generally supported the proposed mediation model, providing a somewhat complex picture of associations among key concepts in terms of which component of confirmation was associated with certain components of body image and through which mediator varied as a function of parental sex. Unlike parental sex, child sex played a minimal role in the current study. This research underscores the utility of employing a confirmation perspective in understanding the mechanisms of how family interactions are related to body image.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjE4Nzc3NTc1